Газопарові міні-ТЕЦ на базі промислових котелень і газотурбінних установок - Reysig V.A.; Tkachenko S.I.; Bujinskiy V.V.; Chepurniy M.N. (General Energy Institute of the National Academy of Sciences of Ukraine, 2004)
Basis indicators of mini-heating plant with gas turbines operation, where working substance is gas-steam mixture, are determined. Expediency of re-equipment industrial boilers at gas-steam heating plant are substantiated.